The brain’s sense of walking: a study on the intertwine between locomotor imagery and internal locomotor models in healthy adults, typically developing children and children with cerebral palsy - Iosa, Marco; Zoccolillo, Loredana; Montesi, Michela; Morelli, Daniela; Paolucci, Stefano; Fusco, Augusto (Frontiers in Human Neuroscience, 2014)
Motor imagery and internal motor models have been deeply investigated in literature. It is well known that the development of motor imagery occurs during adolescence and it is limited in people affected by cerebral palsy. However, the roles of motor imagery and internal models in locomotion as well as their intertwine received poor attention. In this study we compared the performances of healthy adults (n=8, 28.1±5.1 years old), children with typical development (n=8, 8.1±3.8 years old) and children with cerebral palsy (n=12, 7.5±2.9 years old), measured by an optoelectronic system and a trunk-mounted wireless inertial magnetic unit, during three different tasks. Subjects were asked to achieve a target located at 2 or 3m in front of them simulating their walking by stepping in place, or actually walking blindfolded or normally walking with open eyes. Adults performed a not significantly different number of steps (p=0.761) spending not significantly different time between tasks (p=0.156). Children with typical development showed task-dependent differences both in terms of number of steps (p=0.046) and movement time (p=0.002). However, their performance in simulated and blindfolded walking were strictly correlated (R=0.871 for steps, R=0.673 for time). Further, their error in blindfolded walking was in mean only of -2.2% of distance. Also children with cerebral palsy showed significant differences in number of steps (p=0.022) and time (p<0.001), but neither their number of steps nor their movement time recorded during simulated walking were found correlated with those of blindfolded and normal walking. Adults used a unique strategy among different tasks. Children with typical development seemed to be less reliable on their motor predictions, using a task-dependent strategy probably more reliable on sensorial feedback. Children with cerebral palsy showed less efficient performances, especially in simulated walking, suggesting an altered locomotor imagery.